Climate policies in a fossil fuel producing country. Demand versus supply side policies - Taran Fæhn; Cathrine Hagem; Lars Lindholt; Ståle Mæland; Knut Einar Rosendahl (Statistics Norway, Research Department, 2013)
In absence of joint global action, many jurisdictions take unilateral steps to reduce carbon emissions, and the usual strategy is to restrict domestic demand for fossil fuels. The impact on global emissions of such demand side policies is found by accounting for carbon leakage, i.e. changes in emissions abroad induced by the domestic action. Another domestic option for fossil fuel producers, that is yet not well explored, is to reduce own supply of fossil fuels, again accounting for leakages. We explore analytically and numerically how domestic demand and supply side policies affect global emissions, contingent on market behaviour in the fossil fuel markets. Next, we combine this with costs of demand- and supply side policies to find the cost-effective combination of the two types of policies. Norway is the case in our numerical analysis. Our results indicate that given a desire for domestic action and a care for global emissions, the majority of emission reductions should come through supply side measures, i.e., by downscaling Norwegian oil extraction.
Keywords: H23; Q41; Q54; 330; Climate policies; Carbon leakages; Oil extraction; Supply side climate policies; Demand side climate policies